Janus kinase inhibitors: between prescription authorization and reimbursability - F.R. Spinelli; F. Conti; R. Caporali; F. Iannone; F. Cacciapaglia; on behalf of the Steering Committee of the Italian Society of Rheumatology (Reumatismo, 2023)
Following the restrictions on the reimbursability of Janus kinase inhibitors introduced by the Italian Medicines Agency, the Italian Society of Rheumatology has drafted this document to shed light on the clinical conditions and reimbursability criteria set out in the prescription forms.